Pengaruh Pengungkapan Kinerja Lingkungan, Kinerja Sosial dan Kinerja Ekonomi terhadap Nilai Perusahaan pada Sektor Pertambangan dan Energi yang Terdaftar di BEI Periode 2019-2023 - Sherly Amalia Rahmah; Nur Ainiyah; Nurdiana Fitri Isnaini (Pajak dan Manajemen Keuangan, 2024)
Sustainability report disclosure is becoming increasingly important for companies, and this can be seen from several perspectives, including corporate social responsibility (CSR), and investor confidence. This study aims to analyze the effect of disclosure of environmental, social, and economic performance on company mining sector on the IDX for the period 2019-2023. Using quantitative method with multiple linear regression through SPSS 25, the sample was taken with purposive sampling with a population of companies in the mining sector listed on the IDX. Sustainability report disclosure is measured using the GRI G4 index, while firm value is measured by Market to Book Value. The results show that environmental, social, and economic performance each has a positive and significant effect on firm value. Simultaneously, the three variables also have a significant influence on firm value.